EXPERIMENTAL STUDY OF THE INTERACTION BETWEEN AMPHIBOLITE AND GRANITE MELT AT 800°C AND 7 KBAR - Khodorevskaya L.I. (My University, 2001)
Interaction between plagioclase amphibolite and synthetic glass of haplogranitic composition in the presence of aqueous fluid was studied experimentally at 800-950°C and 7 kbar. Amphibolite is replaced by granite with the development of a succession of zones, whose composition depends on the temperature. The zoning produced at 800°C was as follows: |granitic melt |Bt + Hbl + melt|Hbl + Bt + Pl + melt|. The crystallization of the melt produces quartz, plagioclase, and potassic feldspar and makes it possible to compare the experimental zoning with its naturally occurring analogues, which were formed during granitization of mafic metamorphic rocks, such as amphibolites and mafic granulites (crystalline schists). The zoning developing at 950°C is as follows: |granitic melt |Opx + granitic melt |granitic melt|Hbl + Bt + Cpx + melt|Hbl + Bt + Cpx + Pl + melt|. The mineral assemblages developing in each zone after melt crystallization are similar to the mineral assemblages described in granitoids of the charnockite series. The paper reports the composition of the mineral phases and chill glass and the variations in concentrations of the latter over the sample. The addition and removal of major oxides are evaluated for each of the zones. It is demonstrated that the replaced amphibolite is bleached near the contact due to the leaching of Mg and Fe and addition of alkalis, which diffuse from granite. The granitic melt is enriched in mafic components in the contact zone.